THE EFFECT OF FEEDING BROILER FARM WASTE-BASED CONCENTRATE ON THE PERFORMANCE OF GROWER-PHASE BALINESE PIGS - H., Sitinjak; Ariana, I N. T.; Sutama, I N. S. (Jurnal Peternakan Tropika; Vol 12 No 4 (2024): Vol. 12 No. 4 Tahun 2024; July - August, 2024)
This study aims to determine the appearance of Balinese pigs after being fed with Concentrate Feed Based on Broiler Farm Waste (KPLA). This research was conducted in the pigsty of Bukit Jimbaran Research Station/Farm, Faculty of Animal Science, Udayana University, South Kuta, Badung Regency - Bali. With three treatments and five replications. The first treatment, (Ration A) using 24% CP.152 Concentrate + 0% KPLA (control). The second treatment, (Ration B) using 12% CP.152 Concentrate + 12% KPLA. The third treatment, (Ration C) using 0% CP.152 Concentrate + 24% KPLA. The variables observed in this study were initial weight, final weight, weight gain, feed consumption, and Feed Convertion Ratio (FCR). Convertion Ratio (FCR). The results obtained in the study on the final weight variable (Kg) A (13.92), B (13.17), and C (13.01); weight gain showed the results of A (41.90), B (42.06), and C (41.12); feed consumption got the results of A (123.04), B (123.04), and C (123.04); FCR showed the results of A (4.42), B (4.27), and C (4.38). The results obtained in each variable showed no difference in each treatment. So It can be concluded that the use of Concentrate Based on Broiler Farm Waste (KPLA) as a substitute for concentrate in feed has no effect on the growth performance of grower phase Balinese pigs. Thus, it can be concluded that the provision of KPLA with a concentration of 12% and 24% is the same as the control.